ChemInform Abstract: Copper‐Catalyzed N‐Arylation of Tautomerizable Heterocycles with Boronic Acids and its Application to Synthesis of Oxygenated Carbazoles. Issue 31 (14th July 2016) - Kumar, Karampoori Anil; Kannaboina, Prakash; Jaladanki, Chaitanya K.; Bharatam, Prasad V.; Das, Parthasarathi
Abstract: The selective N‐arylation of heterocycles with a series of arylboronic acids under base free conditions at ambient atmosphere is presented.